ANALISIS PESAN-PESAN DAKWAH DALAM SYAIR-SYAIR LAGU OPICK - Yantos Yantos (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
In Islamic, Every body has duty for advising another or It’s called “berdakwah”. There are many medium for “berdakwah”, one of them is by musical art. Some one can writes words in a song to urge another Moslem in order to be the real Moslem. Some one always urges another Moslem to ”amal ma’ruf nahi mungkar”. Almost All the words in Opicks song tells about Islamic Mission example Aqidah, Syari’ah, Akhlak and informatif, persuasive and Coersive. Opick tries to build belief of Moslem in order always to be faithful and guarentee people to get happiness in world living and akhirat living.